Swallowing a cellular automaton pill: Predicting drug release from a matrix tablet. (March 2014) - Buchla, Ezra; Hinow, Peter; Nájera, Aisha; Radunskaya, Ami
Matrix tablets are drug delivery devices designed to release a drug in a controlled manner over an extended period of time. We develop a cellular automaton (CA) model for the dissolution and release of a water-soluble drug and excipient from a matrix tablet of water-insoluble polymer. Cells of the CA are occupied by drug, excipient, water or polymer and the CA updating rules simulate the dissolution of drug and excipient and the subsequent diffusion of the dissolved substances. In addition we simulate the possible fracture of brittle drug and excipient powders during the tablet compression and the melting of the polymer during a possible thermal curing process. Different stirring mechanisms that facilitate the transport of dissolved drug in the fluid in which the tablet is immersed are modeled in the water cells adjacent to the boundary of the tablet. We find that our simulations can reproduce experimental drug release profiles. Our simulation tool can be used to streamline the formulation and production of sustained release tablets.